Non-pharmacological Randomised Control Trial: Green Coconut (Cocos nucifera L.) Water to Reduce Dysmenorrhea Pain - Nugroho, Fajar Ari; Putri, Oktaviana Manda; Sariati, Yuseva (Jurnal Kedokteran Brawijaya, 2020)
Dysmenorrhea is a common cause of pain in young women. The discomfort of dysmenorrhea causes unstable emotions, sleep disturbances, diet changes, and increased stress and depression that can degrade women quality of life. This non-pharmacological Randomized Controlled Trial aimed to obtain the optimal dose of green coconut water as a magnesium source for reducing dysmenorrhea pain. Twenty-one participants divided into three groups. Treatment group 1 obtained 330 ml of green coconut water, treated group 2 obtained 165 ml of green coconut water, and the control group obtained 330 ml of mineral water where each dose repeated three times every 4 hours. VAS questionnaire used to measure the value of pain intensity before and after administration. The 330 ml green coconut water dose is the effective dose compared to control (VAS=4.14, p=0.000), while another dose has a weak effect (VAS=1.86, p=0.124). This finding proves that green coconut water can be a non-pharmacological alternative in handling dysmenorrhea pain.